Beyond the Choice of What You Put in Your Mouth: A Systematic Mapping Review of Veganism and Vegan Identity - Vestergren, Sara; Uysal, Mete Sefa (Frontiers in Psychology, 2022)
In recent years, and in the current climate crisis, the interest in veganism and sustainable diet/lifestyle has increased. This growing interest can also be seen within academia. Therefore, we set out to systematically document and organise the social psychological literature on veganism and vegan identity to identify where the field currently is, and what we need to do next. Following PRISMA guidelines we identified a data set of 26 academic papers published between 2010 and 2021. Through a thematic analysis of the data, we created four categories of study focus and content: 1) vegans as a disadvantaged/stigmatized group, 2) the role of ideology in negative attitudes toward vegans, 3) the role of moral and ethical beliefs in changing or sustaining dietary preferences, and 4) veganism as a social movement and vegan activism. Our analysis emphasises issues with merging all non-meat eaters, reduction of veganism into dietary or lifestyle choices neglecting the politicised content and movement, lack of processes underlying emergence and endurance of veganism, and decontextualization of vegan identity. What is needed is a more fine-grained exploration that addresses the identified issues to account for the content of vegan identity. This would expand, for example, the motives literature to include and emphasise intersectionality in a vegan identity context. Specifically, to facilitate a more sustainable lifestyle, the content of social dimensions needs to be qualitatively explored.